Respuesta :
The gradient of this line is 9 so the gradient of the perpendicular line is -1/9 (the two perpendicular gradients must multiply to get -1).
The equation of a line is y=mx+c
where m is the gradient and c is the y intercept
We can then just substitute values in:
y = -1/9(x) -2
The equation of a line is y=mx+c
where m is the gradient and c is the y intercept
We can then just substitute values in:
y = -1/9(x) -2
y=mx+b
m=slope
b=yint
slopes of perpendicular lines multiply to -1
y=9x+1
9 times what=-1
what=-1/9
yint=-2
too easy
slope=-1/9=m
ying=-2=b
y=-1/9x-2
m=slope
b=yint
slopes of perpendicular lines multiply to -1
y=9x+1
9 times what=-1
what=-1/9
yint=-2
too easy
slope=-1/9=m
ying=-2=b
y=-1/9x-2